Навершя Чмиревої Могили - Попандопуло, З.Х. (Археологія і давня історія України, 2019)
Статтю присвячено одному з найцікавіших артефактів скіфського часу — навершям у вигляді бубонця з крилатим орлиноголовим грифоном з левовим торсом, виявленим поблизу підніжжя знаменитого кургану Чмирева Могила. До наукового обігу вводяться три відносно нових знахідки такого типу, на фоні аналогій розглядаються їх художні особливості, питання призначення та хронології. In 1977 on the site of famous burial mound Chmyrеva Mohyla located on the northern outskirts of Velyka Bilozerka village of Zaporizhzhia region three bronze pole-tops with images of gryphons were found by local people on the plowed field. There is no evidence whether other artifacts have been found. Luckily nearby in Gunovka village the expedition of Institute of Archaeology of National Academy of Sciences of Ukraine was working under the leadership of Yu. V. Boltryk who got the founded artifacts and then sent them to Zaporizhzhia regional museum of local lore, history and economy.